Energy, exergy, and sustainability a novel comparison of conventional gas turbine with fuel cell integrated hybrid power cycle. (19th September 2022) - Sinha, Abhinav Anand; Choudhary, Tushar; Ansari, Mohd. Zahid; Shukla, Anoop Kumar
Abstract: In this paper, six novel modified exergy relations are explored to determine the precise estimation of exergy destruction and to identify which component has the most improvement potential. For this, three power generation cycles are considered, i.e., simple gas turbine (SGT), recuperated gas turbine (RGT), are compared with a novel hybrid system (SOFC-RGT: Solid Oxide Fuel Cell-RGT), which operates with fuel flexibility as well as enhanced work-output and thermal efficiency. For energy, exergy, and sustainability studies, numerical modeling is conducted using MATLAB. At rp  = 4, TIT = 1250 K, an exclusive comparison has been made between proposed configurations based on thermodynamic modeling and exergy-based sustainability index. It is found that with the inclusion of a recuperator and a fuel cell in the proposed cycles, the thermal and sustainability performance tend to increase significantly. Whereas, exergy destruction increases but has minimal impact on comparing thermal performance and sustainability index. In terms of sustainability, RGT is 30.76% more sustainable than SGT, while SOFC-GT is 63.39% more sustainable than RGT. Graphical abstract: Image 1 Highlights: The gas turbine exhaust waste heat generated has been examined for powering the fuel cell. A comparative sustainable, qualitative and quantitative performance comparison has been made between SGT, RGT and SOFC-RGT. As per sustainability index the performance order is SGT < RGT < SOFC-RGT (lower to higher). 6-Modified exergy indicator is used for performance comparison. A novel performance map has been drawn for SGT, RGT and SOFC-RGT.